Karakteristik Perjanjian Jual Beli Tanah yang Belum Terdaftar Hak Atas Tanah - I Gusti Bagus Andika Bagaskara; I Ketut Kasta Arya Wijaya; Luh Putu Suryani (Fakultas Hukum Universitas Warmadewa, 2021)
Government Regulation Number 24 of 1997 concerning Land Registration, the Government requires all of the land to register their land with the competent authority, but in society there are still lands that have not registered the phenomenon, so to ensure legal certainty for all overland. Then land that has not been registered must be registered. From the aspect of legal and procedural risks, it will be different from registered lands if the transfer of land rights is carried out. There are two problem formulations discussed in this paper 1. What are the characteristics of the sale and purchase agreement whose land has not been registered? 2. What is the legal certainty for the sale and purchase agreement of land rights that have not been registered? In writing this thesis using normative legal research, normative legal research requires legal materials including primary legal materials and secondary legal materials. The results from the study can be argued that the legal risk aspect is more prone to occur compared to land that has been registered, then from the procedural aspect are different from land that has been registered where the land was not registered requires precision so as not to cause legal problems.